IMPLEMENTASI KEBIJAKAN ETLE DALAM MENINGKATKAN TERTIB BERLALU LINTAS MASYARAKAT DKI JAKARTA - Athalla Putra, Nanda; Larasati Setianingsih, Endang; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
DKI Jakarta is the province with the highest number of traffic violations in Indonesia every year, as seen in the 2022 National Police data (Pusiknas) reaching 655,176 above East Java, West Java, Central Java and Banten. The police, which has a big responsibility in handling traffic problems, has made a breakthrough, namely ETLE which is also the application of e-government in the ticketing system. ETLE itself is regulated in Law Number 22 of 2009 Article 272 on Road Traffic and Transportation. The purpose of implementing this ETLE policy is to increase public awareness in traffic and to always monitor traffic violations anywhere and anytime so that the safety and security of the public of motor vehicle users is guaranteed. This study aims to find out the implementation of the ETLE policy and what are the inhibiting factors in the process of implementing ETLE in DKI Jakarta by Polda Metro Jaya especially the Directorate of Law Enforcement Sub-Directorate. The method used in this study is a qualitative method where in collecting data using the interview and observation methods and the analysis is in the form of a descriptive form, namely in the form of describing the phenomenon of ETLE implementation in DKI Jakarta in the enforcement of traffic violations. Based on the results of the research, the implementation of ETLE in DKI Jakarta is carried out by recording traffic violators both using static cameras as well as mobile cameras, sending a confirmation letter of violation to the address of the traffic violator, as well as ticket payments that can be made online or offline. The obstacles faced in the implementation of ETLE in DKI Jakarta are the lack of resource facilities such as cameras where the procurement still receives grants from existing stakeholders, namely DISHUB and the lack of public awareness in traffic because the ETLE system itself is still inaccurate.